ZUR ROLLE DER LEHRENDE ALS INTERKULTURELLE VERMITTLER IM DAF-UNTERRICHT - Janku, Marisa; Kërçiku, Xhesjana (POLISSEMA – Revista de Letras do ISCAP, 2020)
This article aims to present the role of the teacher in conveying the intercultural competence in teaching and learning the German foreign language. In view of this purpose, the techniques and strategies used by teachers, and strategies to have an intercultural learning of the German language, will be addressed briefly. The main objective of this study consists in presenting the teaching methods and instruments, important for the transmission of intercultural competence as well as the presentation of subjective views and opinions of German language teachers on the role of communication and intercultural competencies in the learning process. The methodology of the study will be based on the collection of empirical data regarding the role of teachers in intercultural teaching and learning of the German language in Albania, analyzing the data and drawing conclusions. Keywords: German language, intercultural communication, mediators, intercultural teaching, intercultural teaching, teacher